Project management – the way to performance among corporations - PISTOL, Luminiţa; UNGUREANU, Gabriela; VÂRGĂ, Anca (Annals of Spiru Haret University. Economic Series, 2012)
Project management has developed from a simple management philosophy restricted to a few functional areas into a business process that include various areas from global market. Nowadays, most of the corporations are using project management systems to achieve performance on the global market, and they realize that project management and productivity are related.